Researching the Global Environmental Politics of Food - Jennifer Clapp; Phoebe Stephens (A Research Agenda for Global Environmental Politics, 2018)
In a world confronted with escalating environmental crises, are academics asking the right questions and advocating the best solutions? This Research Agenda paves the way for new and established scholars in the field, identifying the significant gaps in research and emerging issues for future generations in global environmental politics.